Does mobile phone instructional video demonstrating sputum expectoration improve the sputum sample quality and quantity in presumptive pulmonary TB cases? Protocol for a prospective pragmatic non-randomised controlled trial in Karnataka state, India - Siddharudha Shivalli; Amrut Hondappagol; Kibballi Madhukeshwar Akshaya; Abhay Nirgude; Narendra Varun; Raveendra Harohally Ramaiah Reddy; Burugina Nagaraja Sharath (BMJ Open)
Introduction Sputum smear microscopy is the cornerstone of tuberculosis (TB) diagnosis under the Revised National Tuberculosis Control Programme (RNTCP) in India. Instructions on how to produce a good sputum sample are a part of RNTCP training manuals, but its assessment is not emphasised. Healthcare provider’s instruction to expectorate a good sputum sample has limitations. Presumptive TB patients often submit inadequate (in quantity and/or quality) sputum samples, which may result in false-negative results. Objectives of the study are, among the selected RNTCP designated microscopy centres in Dakshina Kannada district, Karnataka, India, (a) to assess the effectiveness of mobile phone instructional video demonstrating sputum expectoration on sputum quality and quantity and (b) to explore the mobile phone video implementation challenges as perceived by the healthcare providers.Methods and analysis This is a pragmatic, prospective, non-randomised controlled trial in two pairs of RNTCP Designated Microscopy Centres (located at secondary and primary healthcare facilities) of Dakshina Kannada district, India. Presumptive pulmonary TB patients aged ≥18 years will be included. We will exclude who are severely ill, blind, hearing impaired, patients who have already brought their sputum for examination, and transported sputum. In the intervention group, participants will watch a mobile phone instructional video demonstrating submission of an adequate sputum sample. The control group will follow the usual ongoing procedure for sputum submission. This study would require 406 participants for each group to achieve a power of 90% for detecting a difference of 15% between the two groups. The participant enrolment started in December 2019.Ethics and dissemination Yenepoya University Ethics Committee, Mangaluru, India, has approved the study protocol (YEC-1/158/2019). It complies with the Declaration of Helsinki, local laws, and the International Council for Harmonization-good clinical practices. Investigators will present the results in scientific forums, publish in a scientific journal, and share with RNTCP officers.Trial registration number Clinical Trial Registry of India (CTRI/2019/06/019887).